2011
DOI: 10.1186/1471-2407-11-417
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1, Id1 and EMT in breast cancer

Abstract: BackgroundCyclin D1 is a well-characterised cell cycle regulator with established oncogenic capabilities. Despite these properties, studies report contrasting links to tumour aggressiveness. It has previously been shown that silencing cyclin D1 increases the migratory capacity of MDA-MB-231 breast cancer cells with concomitant increase in 'inhibitor of differentiation 1' (ID1) gene expression. Id1 is known to be associated with more invasive features of cancer and with the epithelial-mesenchymal transition (EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 57 publications
(66 reference statements)
5
66
0
Order By: Relevance
“…Stimulation by its ligands leads to the dissociation of IB from NF-B and degradation through the ubiquitin/ proteasome-dependent pathway (17,18). The released NF-B translocates into the nucleus and activates downstream genes, including matrix metalloproteinase-9 to promote cell invasiveness (19), TRAF1 and -2 to evade apoptosis (2), cyclin D1 to facilitate cell proliferation (29), and the oncoprotein c-Myc, which is also linked to poor cancer outcome (33). Moreover, IB kinases (IKKs) regulate Myc protein stability, further enhancing breast cancer progression (31).…”
mentioning
confidence: 99%
“…Stimulation by its ligands leads to the dissociation of IB from NF-B and degradation through the ubiquitin/ proteasome-dependent pathway (17,18). The released NF-B translocates into the nucleus and activates downstream genes, including matrix metalloproteinase-9 to promote cell invasiveness (19), TRAF1 and -2 to evade apoptosis (2), cyclin D1 to facilitate cell proliferation (29), and the oncoprotein c-Myc, which is also linked to poor cancer outcome (33). Moreover, IB kinases (IKKs) regulate Myc protein stability, further enhancing breast cancer progression (31).…”
mentioning
confidence: 99%
“…For example, ID1 was found to elevate the expression of epithelial mesenchymal markers in nicotine and EGF-induced proliferation, migration and invasion of nonsmall cell lung cancer (23). Similarly, ID1 was found to be positively associated with the migratory and invasive features of breast cancer cells by enhancing epithelial-mesenchymallike markers (28). A clinical observation indicated that ID1 expression was strongly associated with lymph node metastasis in patients with CRC (13).…”
Section: Discussionmentioning
confidence: 84%
“…Changes in gene expression from ALA treatment independent of time were also observed in MDA-MB-231 cells, including a reduction in ID1, and increases in JUN, NME1, and THBS1. The inhibitor of DNA binding protein, ID1, has been linked in MDA-MB-231 cells to cyclin D1 silencing and increased cell migration and invasiveness [43], and angiogenesis [30]. Thus the ability of ALA to reduce the expression of ID1 in MDA-MB-231 cells may lead to decreases in cell growth.…”
Section: Discussionmentioning
confidence: 99%